First record and a new species of Megarthrus Curtis (Coleoptera, Staphylinidae, Proteininae) from the Colombian Central Andes - López-García, Margarita M.; Méndez-Rojas, Diana M.; Navarrete-Heredia, José Luís (Zootaxa, 2011)
The genus Megarthrus Curtis 1829 with about 139 species described around the world, is the largest of the subfamily Proteininae (Coleoptera: Staphylinidae) (Cuccodoro 2011). Megarthrus is distributed worldwide (Cuccodoro 1999) but it is apparently more diverse in the Holartic region (Navarrete-Heredia et al. 2002). However, the South American fauna is underestimated because many of the collected specimens are not yet described (Cuccodoro 2011). Newton et al. (2005) cited the genus as probable in Colombia because some species are known from Central America and northern South America, but until now, no species has been published from Colombia. Therefore, M. andinus sp. nov. represents the first record of the genus and subfamily for this country.